Pamięć o powstaniu zabajkalskim 1866 roku. Forma upamiętnienia powstania zabajkalskiego w ramach powstającego w Białymstoku Muzeum Pamięci Sybiru - Śleszyński, Wojciech (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2018)
The Siberian Uprising of 1866 – the last military stage of the January Uprising remains vivid in the local Siberian memory. The uprising and Polish explorers of Siberia are a vital part of the local heritage. In Poland, contrastively, the memory of the Siberian Uprising looks different. Therefore, apart from science or popular science articles and commemorative staging, it seems reasonable to look for a permanent and attractive way of memorializing this historical episode. The uprising can stay in the collective memory of the Poles owing to the Sybir Memorial Museum in Białystok. The exhibition of the 19th century Siberia will be located on the second floor of the museum’s building and will be a separate section of the institution. This section will accommodate a permanent exhibition of the events that took place near Lake Baikal in 1866: the beginning of the rebellion in Kułtuk, the rebellion around the southern part of Lake Baikal and the execution of the uprising’s main leaders in the suburbs of Irkutsk.